BIPLOT UNTUK MENGETAHUI KARAKTERISTIK KABUPATEN/KOTA DI JAWA TENGAH BERDASARKAN PRODUKSI BAWANG PUTIH, BAWANG MERAH, CABE BESAR DAN CABE RAWIT - Safitri, Diah; Suparti, Suparti; Pratiwi, Esti; Estiningrum, Tyas (MEDIA STATISTIKA, 2014)
Biplot is a graphical representation of a data matrix. Garlic, onions, chili, and thai pepper are important plant in Indonesia because most people in Indonesia especially in Central Java consume garlic, onions, chili, and thai pepper every day. In this research, districts in Central Java seen characteristics are based on the productions of garlic, onions, chili, and thai pepper using biplot. There are highly correlation between chili and thai pepper, which means districts that have highly productions of chili will also tend to have highly production of thai pepper. There are some districts have the production of  garlic, onions, chili, and thai pepper relatively low, and there are some of the city has zero production of  garlic, onions, chili, and thai pepper.   Keywords: Biplot, Production of  garlic, onions, chili, thai pepper